Measuring taxes on income from capital: Evidence from the UK - Michael P. Devereux; Alexander Klemm (Institute for Fiscal Studies (IFS), 2003)
This paper explores the properties of alternative measures of the taxation of income from capital, by applying them to data for the UK over the last thirty years. We consider several types of measures, reflecting both average and marginal rates.
Keywords: 330; Kapitalertragsteuer; Steuerbelastung; Großbritannien